2011
DOI: 10.1128/aac.00007-10
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis embB Codon 306 Mutations Confer Moderately Increased Resistance to Ethambutol In Vitro and In Vivo

Abstract: Ethambutol (EMB) is a major component of the first-line therapy of tuberculosis. Mutations in codon 306of embB (embB306) were suggested as a major resistance mechanism in clinical isolates. To directly analyze the impact of individual embB306 mutations on EMB resistance, we used allelic exchange experiments to generate embB306 mutants of M. tuberculosis H37Rv. The level of EMB resistance conferred by particular mutations was measured in vitro and in vivo after EMB therapy by daily gavage in a mouse model of ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…It has also been shown that there is a narrow range between the MICs of EMB-susceptible and EMBresistant isolates of M. tuberculosis (15,47). Some mutations, e.g., the M306I substitution, give rise to a modest increase in the MIC (37,44,52), which may explain why this particular mutation was found in so many EMB-susceptible isolates in this study. It is likely that the EMB MIC increases only moderately for the embB A313V substitution, as we detected it in a phenotypically resistant isolate, and others have found it in EMB-susceptible isolates (6).…”
Section: Discussionsupporting
confidence: 53%
“…It has also been shown that there is a narrow range between the MICs of EMB-susceptible and EMBresistant isolates of M. tuberculosis (15,47). Some mutations, e.g., the M306I substitution, give rise to a modest increase in the MIC (37,44,52), which may explain why this particular mutation was found in so many EMB-susceptible isolates in this study. It is likely that the EMB MIC increases only moderately for the embB A313V substitution, as we detected it in a phenotypically resistant isolate, and others have found it in EMB-susceptible isolates (6).…”
Section: Discussionsupporting
confidence: 53%
“…This mutation has been observed to cause both low-level and high-level resistance to ethambutol and so may lead to a borderline phenotype (21,22). The isolate from patient 15 was phenotypically ethambutol sensitive but had a Q497R mutation in the embB gene, which has previously been associated with sensitivity both in clinical isolates (23) and through the construction of isogenic mutants (24), and so was discounted.…”
Section: Resultsmentioning
confidence: 99%
“…These genes are ubiquitous in mycobacteria and have no sequence similarity to any identified protein family in other bacteria. Consequently, the accumulation of mycolic acids due to a lack of arabinan receptors for mycolic acids results in cell death [9][10][11].…”
Section: Introductionmentioning
confidence: 99%